(untitled) (Journal of Engineering, 2024)
To study the nonlinear response of composite concrete beams, a finite element analysis is presented. Material nonlinearities as a result of nonlinear response of concrete in compression, crushing and cracking of concrete, strain softening and stiffening after cracking, yielding of reinforcement, bond- slip, shear-slip, and dowel action between the precast concrete beams and the cast-in-situ slabs are considered.A biaxial concrete model is adopted. Concrete is treated as an orthotropic material with smeared rotating crack model. The steel reinforcement is assumed to be in a uniaxial stress state and is modeled as a bilinear material. I A two-dimensional plane stress finite element type is used to model the concrete Reinforcement is represented by one-dimensional bar elements. Bond-slip and dowel action is modeled by using fictitious linkage elements with two springs at right angles. Shear-slip is modeled by using shear transfer in face elements with appropriate stiffness values Comparison between the results obtained by the finite element and available experimental results of composite concrete beams is made. The results compare satisfactorily with the experimental ones